Service rating of UPV CUB cafeteria (Miagao) - Cangayda, Edyell; Fabillon, Jean.; Mendoza, Melany; Pamatian, Jeleen; Reyes, Marla May. (2003)
Executive Summary This study revolved around the determination of CUB Cafeteria's effectiveness based on customer's perception regarding Accessibility, Spatial Convenience, Vnetilation, Taste of the Food, Food Nutrition, Customer Relation, Waiting time, Sanitation, Product Variety and Price. The data used in this study was collected through a structured questionnaire made by the researchers. The smaple size was determined by using a confidence interval approach and a stratified sampling was employed. The respondents were divided into students, faculty, and personnel/staff. The researchers used both descriptive and inferential analysis. Descriptive analysis includes the frequency of the respondents who eat/do not eat at the CUB Cafeteria, the frequency of the respondent's visitation, and the time of visitation. It also consists the mean ratings of the respondents on the status of the CUB Cafeteria with regards to certain criteria. In addition, the frequency of the respondent's reason of not eating in the CUB Cafeteria was also discussed. On the other hand, inferential analysis tackled the respondent's perception on the CUB Cafeteria's effectiveness when grouped according to occupation, year level, college, STFAP bracket assignment and annual family income by Kruskal Wallis H test.
Marketing Research (BA 174- Marketing Research) -- Iloilo City : UPV-CM, October 20, 2003.